The Impact of Cue Card Media on the Secondary School Students’ Speaking Anxiety - Nursalim, Nursalim; Fahrurrozi, Nurmas Jihad (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
The objective of this research is to find out whether a cue card media given impact or not in reducing speaking anxiety at grade in MTs Az-Zikra Kota Sorong. Related to the objective of the researcher used pre-experimental qualitative research design. The design of this research is pre-experimental research. The population of this research was eighth grades students with total of the sample was 34 students, based on purposive sampling. In the collecting the data, the researcher used 32 items questionnaire for pre-test and posttest. In analyzed the data, the researcher used SPSS 20 program to calculation the data. The result of the research showed that, there is a difference in the scale between the before treatment and after treatment because T-value (6.258) > T-table (1.703) and P value (0.000) < ? (0,05). It also indicates that the H0 was rejected and Ha which said Cue card media give impact on the student speaking anxiety was accepted. It can be seen from the mean score from the pre-test questionnaire was 76,4 decreased on post-test questionnaire was 53,6. It can be concluded that cue card media can reduce the students’ speaking anxiety.